Effect of Meropenem Restriction on Time Between Order and Administration in a Medical Intensive Care Unit. (October 2020) - Le, Aline; Kang, Le; Noda, Andrew; Godbout, Emily; Markley, John Daniel; Lee, Kimberly; Pakyz, Amy; Kim, Jihye; Doll, Michelle Elizabeth; Bearman, Gonzalo; Stevens, Michael
Abstract : Background: In this study, we assessed whether meropenem restriction led to delays in administration for patients in a medical intensive care unit (MICU) at a large tertiary-care urban teaching hospital. Methods: The antimicrobial stewardship program (ASP) at Virginia Commonwealth University Health System (VCUHS) requires approval for restricted antimicrobial orders placed between 8 a . m . and 9 p . m . Between 8 a . m . and 5 p . m . (daytime), authorized approvers include ASP and infectious diseases (ID) physicians. From 5 p . m . to 9 p . m . (evening) orders are approved by ID fellows. Orders were entered as Stat, Now, and Routine. Between 9 p . m . and 8 a . m . (night), patients receive doses without approval. Meropenem restriction began in mid-January 2018. Pre- and postmeropenem restriction periods were defined as February–December 2017 and February–December 2018. Meropenem use data were compared for adult patients in the MICU. A multivariable Cox regression model was implemented to compare (1) time from order entry to approval; (2) time from order approval to patient administration; (3) total time from order entry to patient administration, adjusting for order priority, approver (ASP, ID consult, ID fellow, pharmacy); and (4) time of day of order placement (day, eve, night). The analyses were performed using SAS version 9.4 software (SAS Institute, Cary, NC). Result: Time from order approval to patient administration was significantly decreased in the postrestriction period (HR, 1.840; P < .001) (Table 1). Stat orders were faster compared to routine orders for order entry to approval (HR, 1.735; P < .001), approval to administration (HR, 2.610; P < .001), and total time from order entry to administration (HR, 2.812; P < .001). No significant differences were found in time to approval by approving service. Time from order entry to approval was faster for nighttime orders than for daytime orders (HR, 1.399; P = .037). Conclusions: Our data indicate that the time from order entry to administration decreased following meropenem restriction in our MICU. More research is needed to identify the reason for this finding, but we postulate that this is due to an effect on drug administration prioritization within nursing workflow. These data will inform our local meropenem restriction efforts. Funding: None Disclosures: Michelle Doll reports a research grant from Molnlycke Healthcare.